Perkembangan Berpikir Kritis pada Anak Usia Dini (Tinjauan Filsafat Ilmu dalam Pendidikan Awal) - Pangestu, Anik Mukti Dwi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research explores the development of critical thinking in early childhood (0-6 years) through a philosophy of science approach. This research discusses children's critical thinking skills, including questioning, viewpoint formation, rationality, information seeking, and analysis. This research uses the literature review method, namely data obtained through literature from journals, articles, and book references to form a solid foundation with the analysis techniques carried out, namely data reduction, data presentation, and conclusion drawing. The results of this study on the ontological, epistemological, and axiological aspects contribute to a deeper understanding of the role of philosophy of science in shaping children's critical thinking from an early age.